Promoting public value by implementing reverse logistics in the South African Police Service - Elphy Mthabini; Adrino Mazenda; Tyanai Masiya (Journal of Transport and Supply Chain Management, 2020)
Background: Effective supply chain management (SCM) processes across all South Africa’s three spheres of government has become critical in view of increasing demand for public services amidst scarcity of resources.